Efeito da inclinação e do número de implantes em próteses totais fixas implantossuportadas : análise de elemento finito não linear com modelo tridimensional - Geremia , Tomás (2014)
The aim of this study was to evaluate the influence of the number of implants and the distal tilting of posterior implants (27 degrees) on the resulting tensions in periimplant bone, abutment screw and prosthetic screw of mandibular full-arch fixed implant supported prosthesis, using a nonlinear finite element analysis. Six virtual models were created, simulating a mandibular full-arch prosthesis with a metallic framework: models with five parallel implants (5R) and with tilted posterior implants (5I); models with four parallel implants (4R) and tilted posterior ones (4I); and models with three parallel implants (3R) and with tilted posterior implants (3I). The Von Mises tensions were analyzed, on a qualitative aspect, on the three regions of interest. The results showed that tilting the posterior implants resulted in higher tensions on the periimplant bone region.Also, the implant placed adjacent to the loading area presented the higher stress magnitudes on the three regions of interest, during all the simulations. Within the limitations of this study, it's possible to conclude that tilting the posterior implants without distalizing the implants platforms, can represent higher Von Mises tensions on the cortical periimplant bone. Still, that the use of three implants supporting a mandibular full-arch prosthesis generated higher stress values on the analyzed regions, when compared to the models simulating four and five implants.